Artificial intelligence : teaching machines to think like people : perspectives from leading practitioners in AI and the science of the brain - Clark, Jack (O'Reilly Media, 2017)
Now that artificial intelligence researchers have used reinforcement learning and deep learning to achieve several notable successes in the areas of perception and action, some AI scientists are turning to the brain for inspiration about what to build next. In this report, author Jack Clark interviews five prominent AI researchers to learn about the growing connections between AI and cognitive science, neuroscience, and developmental psychology.